Contesting neoliberal governance. The case of Romanian Roma - Anghel Ionuț-Marian (Social Change Review, 2015)
The article delineates the shifting forms of minority governance that took shape after 1989 in solving Roma related affairs and its ambiguous effects on the ground. I argue that, after 1989, the new social and public policies adopted a more neoliberal trend in solving Romani affairs through processes of decentralization, public-private partnerships and mobilization of civil society (Roma) organizations as key tools for empowering and social inclusion of Romani communities, abandoning old governmental programs focused on discipline, control and policing. However, as we will see in the Romanian case, these processes and policies had ambiguous effects and often have gone together with a diminishing of democratic accountability and control of Roma related affairs by state/public institutions and with the devolution of responsibilities to non-governmental and human rights organizations, Roma representatives from public institutions and communities themselves (see also van Baar 2011a).